Maid Tracers: Maid Matching Management System (3Ms) : Technical Report - Bansir, Fasya; Salleh Huddin, Nur Aliah; Mohd.Nizam, Nur Athirah Aqilah; Omar, Abdul Halim (Multidisciplinary Applied Research and Innovation, 2022)
Managing a house is quite difficult especially for those who are always busy with work matters,and also those who have a large number of family members or live in a large house.Finding a maid is quite difficult at this time and situation due to the presence of the Covid-19 epidemic,doubts in the selection of maids as well as the limited and tight time of employers make it difficult to find maids.Such as,an online maid service search and booking system is very suitable to be built at this time. The Maid Tracers that will be developed does not require eVisa on each employee(Maid)it is because this system has certain conditions that the employee must be a Malaysian citizen and reside in Malaysia to reduce the entry of outsiders into Malaysia. The method to implement this project is structured Structured Analysis and Design Methodology with using System Development Life Cycle and Waterfall Model. This system gives a positive impact to others because they can choose any maid to avoid bad problems such as theft and robbery.In conclusion,the system can ease the employers who are finding a maid with the requirement that they need it because the system has listed all the maid details.